Correlation of band electronic structure with efficiency in perovskite solar cells with vanadium (Ⅳ) oxide thin film buffers - Eom, Kiryung; Yoo, Il Han; Sial, Qadeer Akbar; Seo, Hyungtak (Current Applied Physics, 2021)
Perovskite solar cells have been studied extensively in the area of perovskite solar cells because they have a comparatively free hysteresis. Through fabrication of a perovskite solar cell based on a vanadium oxide buffer, this study clarified the mechanism of electron and hole transport in the laminated layer upon irradiation with light. The power conversion efficiency (PCE) of the Vanadium (Ⅳ) oxide (VO2) sputtering process device was approximately 13% and with the spin-coating process was 8.5%. To investigate the physicochemical origin of such PCE differences depending on the process type, comprehensive band alignment and band structure analyses of the actual cell stacks were performed using X-ray photoelectron spectroscopy depth measurements. Accordingly, it was found that the inconsistent valence band offset between the perovskite absorption layer and V2O5 layer as a function of the VO2 process type caused a difference in the hole transport, resulting in the difference in the efficiency.
Keywords: Absorption layer; Band structure analysis; Depth measurements; Oxide thin films; Power conversion efficiencies; Spin coating process; Sputtering process; Valence band offsets; Band alignment; Band offset; PCE; Perovskite solar cells; Vanadium oxide; XPS